So it is given that
S(n) = 5n^2 + 3n
And you want to find the arithmetic progression and the nth term.
Recall that the sum of an arithmetic progression is given by the formula:
S(n) = n(2[a1] + (n - 1)d) / 2
{Note: a1 represents the unknown first term, and d represents the difference between consecutive terms}
Through algebraic manipulation with which I won't show the details, we can replace S(n) to be
S(n) = (d/2)n^2 + n(a1 - d/2)
BUT
S(n) = 5n^2 + 3n, so all we have to do is equate the coefficients of n^2 and the coefficients of n.
d/2 = 5 (implies d = 10)
a1 - d/2 = 3 (implies a1 = 8)
Therefore, a1 (our first term) is equal to 8, and d = 10.
Our sequence then goes as follows;
8, 18, 28, 38, 48, ...
with our general term being 8 + (n - 1)10, or (8 + 10n - 10), or
(10n - 2)
Conclusion:
The arithmetic progression is the sequence with a1 = 8 and r = 10, and
a[n] = (10n - 2)
Edit:
---
If you're interested in knowing the details of how I got from
S(n) = n(2[a1] + (n - 1)d) / 2
to
S(n) = (d/2)n^2 + n(a1 - d/2)
Here it is, below.
S(n) = n(2[a1] + (n - 1)d) / 2
Factor out a 1/2, since it's a fraction anyway.
S(n) = (n/2) (2[a1] + (n - 1)d)
Expand the inside.
S(n) = (n/2) (2[a1] + nd - d)
Distribute the (n/2)
S(n) = (a1)n + d(n^2)/2 - dn/2
Group together the n^2 terms and the n terms.
S(n) = d(n^2)/2 + (a1)n - dn/2
S(n) = (d/2)n^2 + (a1 - d/2)n
It was only through this algebraic manipulation that we could equate this component-wise with our given sum.
2006-12-22 19:55:47
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
Sn = 5 n^2 + 3n
S1 = 5 + 3
= 8 is the first term(a)
S2 = 5*4 + 3*2
= 26 is the sum of first two terms
second term = 26 -8
= 18
S3 = 5*9 + 9
= 54 is the sum of first three terms
third term = 54 - 26
= 28
A.P is 8,18,28,..
a= 8, d = 10
nth term = a + (n-1)d
= 8 + (n-1)10
= 10n -2
2006-12-22 22:52:30
·
answer #2
·
answered by george t 2
·
0⤊
0⤋
becuase it is ap let kth term be ak+b
sum of n terms a n(n+1)/2 + bn = an^2/2 + (b+a/2) n
comparing with 5n^2 + 3n
a/2 = 5 oe a = 10 and b+5 = 3 or b = -2
nth term = 10n - 2
2006-12-22 21:40:46
·
answer #3
·
answered by Mein Hoon Na 7
·
0⤊
0⤋
S_n = 5n² + 3n
S_(n - 1) = 5(n - 1)² + 3(n - 1)
= 5n² - 10n + 5 + 3n - 3
= 5n² - 7n + 2
Now S_n = S_(n - 1) + U_n
So U_n = S_n - S_(n - 1)
= 10n - 2
So the AP is {8, 18, 28, ...., 10n - 2, ....}
2006-12-23 06:33:47
·
answer #4
·
answered by Wal C 6
·
0⤊
0⤋
Xn = 5(n)^2 + 3(n) - 5(n-1)^2 - 3n + 3
Xn = 5(n)^2 + 3(n) - 5n^2 + 10n - 5 - 3n + 3
Xn = 10n - 2
N = ∑ 8 + 18 + 28 + . . . . . + (10n - 2)
2006-12-22 20:10:32
·
answer #5
·
answered by Helmut 7
·
2⤊
0⤋